2007
DOI: 10.1097/hjh.0b013e3280287a72
|View full text |Cite
|
Sign up to set email alerts
|

Effect of losartan, compared with atenolol, on endothelial function and oxidative stress in patients with type 2 diabetes and hypertension

Abstract: This study demonstrates that losartan significantly improved endothelial function in type 2 diabetes patients with hypertension compared with atenolol. This must be independent of the blood pressure-lowering effect of losartan and is probably caused by an antioxidative effect of the angiotensin receptor blocker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 46 publications
1
74
1
5
Order By: Relevance
“…Consistent with these findings, RAAS inhibition with the ARB losartan has previously been shown to reduce levels of F 2 isoprostanes in patients with type II diabetes and hypertension. 32 However, considering the small magnitude of the changes, large variability in the data and lack of statistically significant between-treatment differences in the present study, it is unlikely that the observed differences are of clinical relevance. It should be noted that a normal range in healthy volunteers has not been established for many of these biomarkers, and so it is unclear to what extent regression to the mean might have explained some of the observed changes from baseline with drug treatment.…”
Section: Discussionmentioning
confidence: 53%
“…Consistent with these findings, RAAS inhibition with the ARB losartan has previously been shown to reduce levels of F 2 isoprostanes in patients with type II diabetes and hypertension. 32 However, considering the small magnitude of the changes, large variability in the data and lack of statistically significant between-treatment differences in the present study, it is unlikely that the observed differences are of clinical relevance. It should be noted that a normal range in healthy volunteers has not been established for many of these biomarkers, and so it is unclear to what extent regression to the mean might have explained some of the observed changes from baseline with drug treatment.…”
Section: Discussionmentioning
confidence: 53%
“…Quantification of endothelial dysfunction can predict therapeutic success of pharmacologic intervention, too. Angiotensin-converting enzyme inhibitors (ACE-I) showed clear improvement of endothelial dysfunction in several modalities [92][93][94]. Additional improvement could be shown for add-on spironolactone in chronic heart failure patients [95].…”
Section: Endothelial Dysfunction-a Hallmark Of Cardiovascular Diseasementioning
confidence: 99%
“…16 In a randomized, double-blind, crossover study of men with type 2 diabetes and hypertension, an angiotensin II receptor blocker significantly decreased a marker of oxidative stress (Po0.001) and caused a significant increase of FMD compared with an angiotensin II-converting enzyme inhibitor (P ¼ 0.01). 33 …”
Section: Angiotensin Receptor Blockersmentioning
confidence: 99%